Circulating type 1 vaccine-derived poliovirus may evolve under the pressure of adenosine deaminases acting on RNA. (22nd November 2015) - Liu, Yanhan; Ma, Tengfei; Liu, Jianzhu; Zhao, Xiaona; Cheng, Ziqiang; Guo, Huijun; Xu, Ruixue; Wang, Shujing
Abstract: Poliovirus, the causative agent of poliomyelitis, is a human enterovirus and member of the Picornaviridae family. An effective live-attenuated poliovirus vaccine strain (Sabin 1) has been developed and has protected humans from polio. However, a few cases of vaccine virulence reversion have been documented in several countries. For instance, circulating type 1 vaccine-derived poliovirus is a highly pathogenic poliovirus that evolved from an avirulent strain, but the mechanism by which vaccine strains undergo reversion remains unclear. In this study, vaccine strains exhibited A to G/U to C and G to A/C to U hypermutations in the reversed evolution of Sabin 1. Furthermore, the mutation ratios of U to C and C to U were higher than those of other mutation types. Dinucleotide editing context was then analyzed. Results showed that A to G and U to C mutations exhibited preferences similar to adenosine deaminases acting on RNA (ADAR). Hence, ADARs may participate in poliovirus vaccine evolution.